Tuberculosis and Society in Tromsø 1878-1920 - An Epidemiological Study of Tuberculosis Mortality Within Societal Differences - Kovacevic, Marko (UiT Norges arktiske universitet, 2020)
This thesis historically examines the disease known as tuberculosis in Tromsø town from 1878 to 1920. It explores the effects of gendered, societal, and economic differences upon tuberculosis mortality. It primarily uses quantitative sources, in the form of local burial registers, cadastral registers, annual medical reports and population censuses. The thesis has found that tuberculosis mortality was high in the town compared to the Norwegian average. The early period saw the lowest tuberculosis mortality rates, while a peak was observed around economic crisis in the 1880s, before it gradually declined by 1920, with a variety of factors were found affecting the local population. Gender roles and differences were shown to have an impact on tuberculosis mortality, but they were found to be non-significant. Socioeconomic factors such as; income, occupational hazards, dwelling quality, alcohol and tobacco abuse were found to have considerable impact on tuberculosis mortality to varying degrees.